Analisis Karakter Kreatif dalam Pembelajaran Seni Tari Kelas IV SDN 4 Caringin - Elisa Fitri; Din Azwar Uswatun; Irna Khaleda (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
Schools is a place to develop the abilities that exist in students. This study aims to describe the creative character of students in learning dance. This research was conducted on fourth grade students of SDN 4 Caringin. This research approach uses a descriptive qualitative approach to determine creative characters in dance learning and data analysis techniques using the Miles and Huberman models. The subject of this research is the fourth grade homeroom teacher at SDN 4 Caringin. Data collection techniques using semi-structured interviews, and documentation. This research was carried out on April 25, 2021 until May 27, 2021. The results of the research that was carried out in class IV SDN 4 Caringin there were four indicators of creative character in learning dance, namely 1) fast and precise, 2) wanting to keep changing and taking advantage of time leisure, 3) new and unique ideas, and 4) flexibility. Based on the results obtained that the four indicators of creative character have or are related to each other with dance learning, it can be seen from the learning process that has been implemented.